Media Pembelajaran Aplikasi Smart Apps Creator Sebagai Optimalisasi Pembelajaran Digital di Sekolah Dasar - Devit Setia Meylindo; A.F. Suryaning Ati MZ; Rizka Novi Irmaningrum (Jurnal Tematik, 2026)
Technological advancements in the Society 5.0 era encourage the education sector to create creative, interactive, and student-centered learning media. In the Elementary Science and Social Studies (IPAS) subject at the primary school level, one common issue is the low level of students’ critical thinking skills, largely due to the continued use of conventional teaching methods. This study aims to develop a Smart Apps Creator-based learning media for the Human Digestive System topic for 5th-grade elementary school students, with a primary focus on enhancing critical thinking skills. This research is a Research and Development study that applies the ADDIE model, which consists of the stages: Analyze, Design, Develop, Implement, and Evaluate. The research subjects were 5th-grade students at SD Muhammadiyah Babat. Research instruments included expert validation sheets, student response questionnaires, and student activity questionnaires. The results showed that the media was categorized as highly valid, with expert validation scores of 93.3% from material experts, 90% from media experts, and 91.7% from design experts. The practicality of the media was also very high, with student response scores above 91%. Therefore, the Smart Apps Creator-based learning media is considered feasible and recommended as a supportive tool for IPAS learning to strengthen students’ critical thinking skills.